Ichnological analysis of the Lower Morne L'Enfer Formation, Cedros Bay, Trinidad, West Indies: evidence of delta asymmetry. (August 2020) - Ali, Shaliza; Wilson, Brent; Gingras, Murray
Abstract: The Pliocene Silt and Sandstone Members of the Lower Morne L'Enfer Formation at Cedros Bay, SW Trinidad, reflect mixed wave, fluvial and tidal influence. Integrated ichnological analyses of these deposits reveal that the prodelta and delta front successions vary notably along-strike. These along-strike variations fit well into an asymmetric delta model. Trace fossil assemblages on the downdrift side of the delta lobe are characterised by diminutive, morphologically simple and facies-crossing forms due to heightened riverine influence. Ichnofossil assemblages on the updrift side of the lobe are robust and diverse, as a result of persistent wave reworking, generally unstressed. Mud- and silt-dominated prodelta and delta front deposits in the downdrift region are characterised by a low abundance and low diversity trace fossil assemblage reflecting a stressed expression of the Cruziana ichnofacies. Slumping and scouring structures are common within the distal prodelta deposits. Prodelta to distal delta front intervals on the updrift side are densely bioturbated. These trace fossil assemblages are abundant and diverse, representing a proximal to archetypal expression of the Cruziana ichnofacies. These deposits coarsen upward into fine grained sandstone beds of the proximal delta front. Strong storm influence in the proximal delta front produced amalgamated tempestite beds void of bioturbation. Lower to middle shoreface deposits comprise fine grained sandstone dominated by robust burrows of suspension feeders attributable to a proximal expression of the Skolithos ichnofacies. Highlights: Integrated ichnological analysis indicate that the Lower Morne L'Enfer Formation was deposited within an asymmetric delta. Updrift regions recorded storm and wave influenced deposits whereas downdrift areas are river dominated. Trace fossil suites within the lower Morne L'Enfer Formation are expressions of the Skolithos and Cruziana ichnofacies.